2020
DOI: 10.3389/fpls.2020.00125
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Function of the NuA4 Complex in Plants

Abstract: Chromatin remodeling plays a key role in the establishment and maintenance of gene expression patterns essential for plant development and responses to environmental factors. Post-translational modification of histones, including acetylation, is one of the most relevant chromatin remodeling mechanisms that operate in eukaryotic cells. Histone acetylation is an evolutionarily conserved chromatin signature commonly associated with transcriptional activation. Histone acetylation levels are tightly regulated throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 141 publications
(313 reference statements)
0
18
0
10
Order By: Relevance
“…Either the complex is attached to the actin filament and moves along the filament propelled by the filament polymerization-depolymerization, or the monomeric actin directly interacts with the chromatin, or other unconventional forms of actin oligomers, performing some (currently unknown) functions in the chromatin remodeling complexes [ 16 ]. Another chromatin-modifying complex is the histone acetyltransferase complex NuA4/TIP60, which is involved in chromatin-binding, histone modifications, transcription, DNA damage response, control of the cell cycle, nonhomologous end joying, and homologous recombination [ 16 , 111 , 112 , 113 ]. Recent studies showed that the SWR1 remodeling complex deposits Htz1 histone into the chromatin and prevents genome instability, which is often associated with tumorigenesis [ 114 , 115 ].…”
Section: Actin Role In Chromatin Organization and Remodelingmentioning
confidence: 99%
“…Either the complex is attached to the actin filament and moves along the filament propelled by the filament polymerization-depolymerization, or the monomeric actin directly interacts with the chromatin, or other unconventional forms of actin oligomers, performing some (currently unknown) functions in the chromatin remodeling complexes [ 16 ]. Another chromatin-modifying complex is the histone acetyltransferase complex NuA4/TIP60, which is involved in chromatin-binding, histone modifications, transcription, DNA damage response, control of the cell cycle, nonhomologous end joying, and homologous recombination [ 16 , 111 , 112 , 113 ]. Recent studies showed that the SWR1 remodeling complex deposits Htz1 histone into the chromatin and prevents genome instability, which is often associated with tumorigenesis [ 114 , 115 ].…”
Section: Actin Role In Chromatin Organization and Remodelingmentioning
confidence: 99%
“…The covalent histone modifications methylation and acetylation are regulated by the antagonistic activity of methyltransferases and demethylases [ 32 34 ] and of acetyltransferases/deacetylases [ 35 37 ], which emerge as complexes such as SET complexes (SET-C) [ 38 ] and histone acetyltransferases complexes (HAT-C). NuA3 [ 39 41 ] and NuA4 [ 42 ] are two classes of HAT-C that function in the acetylation of the histone H3 [ 43 ] and of the histones H4, H2A, and H2A.Z, respectively [ 44 , 45 ]. Each of these complexes comprises multiple members that associate with each other directly or indirectly, and each exhibits different and non-redundant functions [ 46 ], indicating that chromatin remodeling and histone modification are complex processes involving the coordinated action of multiple regulatory elements [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these complexes share common subunits. For example, ARP4, SWC4, YAF9, and RUVBL2 have been found in both NuA4-C and SWR1-C [ 42 , 44 , 47 , 48 ]. The significance of this sharing of components among different complexes is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on Arabidopsis homologs of NuA4 subunits by affinity purification followed by mass spectrometry (AP-MS/MS) suggested that plant NuA4 resembles its yeast counterpart [15][16][17][18] . Importantly, the scaffold subunits Esa1-Associated Factor 1A/B (AtEAF1A/B), Transcription-Associated Protein 1 (AtTRA1) and Enhancer of Polycomb-Like 1A/B (AtEPL1A/B) were shown to be physically associated with the catalytic subunit homologs Histone Acetyltransferase of the MYST family 1/2 (HAM1/2) [16][17][18][19] .…”
mentioning
confidence: 99%
“…Notably, AtTRA1 was also copurified with components of complexes responsible for H2A-H2A.Z exchange, suggesting a link between NuA4dependent histone acetylation and H2A.Z deposition 20,21 . AtEPL1 and AtEAF1 seem to be specific for NuA4, as they were not copurified with other chromatin complexes; thus, they are key to understanding NuA4 function 15,22,23 . In genetic studies, plant homologs of NuA4 subunits have been linked to gametogenesis, ABA responses, flowering time regulation, chlorophyll synthesis, cell growth, and ploidy 17,[24][25][26] .…”
mentioning
confidence: 99%